Downregulated ESRP1/2 promotes lung metastasis of bladder carcinoma through altering FGFR2 splicing and macrophage polarization - Zhao, Yuyang; Li, Mingyang; Wu, Wenbo; Miao, Wenhao; Liu, Haitao (Frontiers in Immunology, 2023)
Lung metastasis occurs in parts of the bladder carcinoma (BC) patients but represents the highest severity and a poor outcome of the disease. The molecular mechanism underlying lung metastasis of BC is not fully understood. Fibroblast growth factor receptor 2 (FGFR2) signaling plays a substantial role in the BC cell growth and invasion. In this study, we assessed the regulation of the alternative splicing of FGFR2 by epithelial splicing regulatory proteins (ESRPs) in lung metastasis of BC. Gene profile of BC in comparison with adjacent non-tumor bladder tissue was obtained from GEO public database to analyze the levels of differentiated genes and pathways. Moreover, the association of ESRP1 or ESRP2 with lung metastasis of BC was analyzed on our own clinic samples. The effects of altered expression of ESRP1 or ESRP2 on alternative splicing of FGFR2 IIIb and IIIc, which represents epithelial and mesenchymal-like splicing, were analyzed on BC cell lines T24 and RT4. The in vivo effects of ESRP1 or ESRP2 on lung metastasis of BC were assessed in mice subcutaneously grafted with ESRP1/2-modified BC labeled with fluorescent and luciferase reporters. We detected significant reduction of ESRP1 and ESRP2 in BC in public database of BC specimens. Moreover, analysis on our own specimens also showed strong downregulation of ESRP1 or ESRP2 in BC, and the latter was more pronounced in cases with lung metastasis. In vitro, altered levels of ESRP1 or ESRP2 caused a switch of FGFR2 splicing between FGFR2-IIIb and FGFR2-IIIc, resulting in changes in tumor cell growth and metastatic potential. In vivo, re-expression of ESRP1 or ESRP2 in BC cells not only inhibited the growth of the xenografted tumor formation in nude mice, but also reduced the occurrence of lung metastasis, partially through altering polarization of tumor-associated macrophages. Our data thus suggest that reduction in ESRP1 or ESRP2 promotes lung metastasis of BC through altering FGFR2 splicing and macrophage polarization.